Filling Empty Seats: How Status and Organizational Hierarchies Affect Exploration Versus Exploitation in Team Design - Perretti, Fabrizio; Negro, Giacomo (Academy of Management Journal, 2006)
Informal and formal mechanisms affect choices between exploitation and exploration in team design. We argue that the status differentiation of team members and differences in organizational structure limit exploration in the form of introducing newcomers to teams and creating new combinations of team members. High- and low-status team members and one- and three-layer organizational structures were expected to be positively related to exploration, and middle-status team members and two-layer structures were expected to be negatively related to it. We used data on 6,446 motion pictures produced by the Hollywood film industry in the period 1929-58 to test our hypotheses.